Advancing the treatment of myopia in children: part 3: Risk to benefit comparison of myopia controlling contact lenses. Issue 10 (October 2021) - Gifford, Kate
Abstract : Dr Kate Gifford offers an analysis of the safety of myopia controlling contact lens wear in childhood compared to the lifetime risks of eye disease and vision impairment associated with myopia.